Development and experimental verification of a generative CAD/FEM model of an external fixation device - Mešić, Elmedin (Array, 2020)
This paper presents the development and experimental verification of a generative CAD/FEM model of an external bone fixation device. The generative CAD model is based on the development of a parameterized skeleton algorithm and sub-algorithms for parametric modeling and positioning of components within a fixator assembly using the CATIA CAD/CAM/CAE system. After a structural analysis performed in the same system, the FEM model was used to follow interfragmentary fracture displacements, axial displacements at the loading site, as well as principal and Von Mises stresses at the fixator connecting rod. The experimental analysis verified the results of the CAD/FEM model from an aspect of axial displacement at the load site using a material testing machine (deviation of 3.9 %) and the principal stresses in the middle of the fixator connecting rod using tensometric measurements (deviation of 3.5 %).The developed model allows a reduction of the scope of preclinical experimental investigations, prediction of the behavior of the fixator during the postoperative fracture treatment period and creation of preconditions for subsequent structural optimization of the external fixator.